Pengajaran Tentang Hari Penghakiman (Amos 5:18—20) - Gusti Dametriana Sihombing; Erickson Nanda Putra Halawa; Grecetinovitria M. Butar-butar (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Judgment is the process of assessing a person's wrongdoing and determining an appropriate punishment, both in worldly and spiritual contexts. In Christianity, the Day of Judgment is when God fully reveals the truth and gives the final verdict on each individual's fate based on their deeds. The Book of Amos, written around the 750s BC by the prophet Amos, warns Israel that the "Day of the Lord," which they anticipated as a day of victory, would actually be a day of darkness and judgment because of their sins. This study examines the relevance of the teachings about the Day of Judgment in the Book of Amos (Amos 5:18-20) to contemporary Christian life. Amos' message emphasizes the importance of living righteously, avoiding sin, and treating others with justice and love. These teachings serve as a guide for Christians to live meaningful and responsible lives before God and others